INTEGRASI KEARIFAN LOKAL DAN KUALITAS LAYANAN DALAM PENGEMBANGAN HOSPITALITY BERKELANJUTAN DI HOTEL FOUR POINTS BY SHERATON MANADO - Helni Desty Yanice Lagarense; Jeskrispen Lagarense; Agustinus Walansendow (Jurnal Hospitaliti, 2025)
This study examines the integration of local wisdom and service quality in the context of sustainable hospitality development at Four Points by Sheraton Manado. A quantitative approach was applied using assumed primary data collected through a survey of hotel guests (n = 120) selected via purposive sampling. A five-point Likert scale questionnaire was employed to assess local wisdom, service quality, and guest satisfaction. Data were analyzed using descriptive statistics and simple linear regression. Findings indicate that the incorporation of local cultural values, Minahasa hospitality, and local product utilization positively and significantly influences guests’ perceptions of service quality. These results confirm that integrating local wisdom not only enhances service quality but also supports sustainable hospitality practices in an international hotel context. This strategy contributes to competitive advantage and authentic guest experiences.